A novel variable curvature clamping anchor for the multilayer CFRP plate cable: Concept, numerical investigation, and design proposals. (September 2022) - Duo, Yongyu; Liu, Xiaogang; Yue, Qingrui; Chen, Hongbing
Abstract: This paper proposed a novel variable curvature clamping anchor (VCCA) for the multilayer carbon fiber-reinforced polymer (CFRP) plate cable and systematically evaluated the anchor performance using the finite element (FE) method. The design concept of the anchor, function of variable curvature waveform, anchor configuration and components design were first presented, then the stress distribution of the CFRP plate with different layers and failure mode of the anchor system were investigated. The six parameters affecting the anchor performance were also studied, including the number of waveforms, bolt preload, anchor length, thickness of ear plate, thickness of clamping plate, and thickness of clip. Finally, the design proposals of the anchor were given. The results indicate that the peak compressive stress has been successfully transferred from the loading end to the back of the anchor, and the interfacial shear stress of the CFRP plate was small and less than one-sixth of the shear strength. In addition, the failure of the anchor system occurred in the cable body part and not inside the anchor. The number of waveforms and the thickness of the clip slightly affected the peak transverse compressive stress, whereas the bolt preload, anchor length, ear plate thickness, and clamping plate thickness had an important influence on the axial stress distribution and peak transverse compressive stress. The novel VCCA proposed in this paper has essential engineering value and significance, filling the gap of the anchor for the multilayer CFRP plate cable, contributing to promoting the application of large-tonnage CFRP plate cable in bridges and space structures, and landing a solid foundation for subsequent experiments.